2020
DOI: 10.4236/ajcm.2020.104029
|View full text |Cite
|
Sign up to set email alerts
|

Third-Order Adjoint Sensitivity Analysis of an OECD/NEA Reactor Physics Benchmark: I. Mathematical Framework

Abstract: This work extends to third-order previously published work on developing the adjoint sensitivity and uncertainty analysis of the numerical model of a polyethylene-reflected plutonium (acronym: PERP) OECD/NEA reactor physics benchmark. The PERP benchmark comprises 21,976 imprecisely known (uncertain) model parameters. Previous works have used the adjoint sensitivity analysis methodology to compute exactly and efficiently all of the 21,976 first-order and (21,976) 2 second-order sensitivities of the PERP benchma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The formulas presented in this work for computing the 4th-order sensitivities of the leakage response to the benchmark's cross sections, along with the formulas presented in [3][4][5][6][7][8][9][10][11][12][13] for computing the 1st-, 2nd-and 3rd-order sensitivities of the PERP benchmark to cross sections can be implemented in both deterministic and Monte-Carlo codes for solving the neutron transport equations. These formulas could be used for sensitivity analysis of reaction-rate responses in subcritical reactors and for subsequent quantification of uncertainties induced in such responses by the uncertainties in the underlying cross sections.…”
Section: Comparison Of Computational Requirements For the 4th-order Sensitivitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The formulas presented in this work for computing the 4th-order sensitivities of the leakage response to the benchmark's cross sections, along with the formulas presented in [3][4][5][6][7][8][9][10][11][12][13] for computing the 1st-, 2nd-and 3rd-order sensitivities of the PERP benchmark to cross sections can be implemented in both deterministic and Monte-Carlo codes for solving the neutron transport equations. These formulas could be used for sensitivity analysis of reaction-rate responses in subcritical reactors and for subsequent quantification of uncertainties induced in such responses by the uncertainties in the underlying cross sections.…”
Section: Comparison Of Computational Requirements For the 4th-order Sensitivitiesmentioning
confidence: 99%
“…These formulas could be used for sensitivity analysis of reaction-rate responses in subcritical reactors and for subsequent quantification of uncertainties induced in such responses by the uncertainties in the underlying cross sections. The 4th-order sensitivity analysis methodology used to produce the results presented in this work, along with the previous sensitivity analysis results reported in [3][4][5][6][7][8][9][10][11][12][13], cannot be obtained by any other methods. The computational times that would be required even by simple-minded finite-difference schemes have been shown to be prohibitive for problems involving as many parameters (21,976) as involved in the PERP benchmark.…”
Section: Comparison Of Computational Requirements For the 4th-order Sensitivitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable the computation of such 3 rd -order sensitivities, Cacuci [12] has recently conceived the "third order adjoint sensitivity analysis methodology for reaction rate responses in a multiplying nuclear system with source" and then applied this general theory to the PERP benchmark in order to derive the exact analytical expressions of the 3 rd -order sensitivities of the PERP benchmark's leakage response with respect to this benchmark's microscopic total cross sections [13] [14] [15]. These works [13] [14] [15] have shown that the largest 3 rd -order sensitivities involve the microscopic total cross section for the lowest (30 th ) energy group of isotope 1 H (i.e., 30 ,6 t σ ). In particular, the largest overall 3 rd -order sensitivity is the mixed 3 rd -order sensitivity ( ) ( ) S σ σ σ…”
Section: Introductionmentioning
confidence: 99%
“…, 429.6 The results obtained in [5]- [10] and [13] [14] [15] indicated that the total microscopic cross section of isotopes 1 H and 239 Pu are the most important parameters affecting the PERP benchmark's leakage response, since they are responsible for the largest 1 st -, 2 nd -and 3 rd -order sensitivities.…”
Section: Introductionmentioning
confidence: 99%